2008
DOI: 10.1146/annurev.nutr.28.061807.155518
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Absorption in the Intestine: The Role of GLUT2

Abstract: Intestinal glucose absorption comprises two components. One is classical active absorption mediated by the Na+/glucose cotransporter. The other is a diffusive component, formerly attributed to paracellular flow. Recent evidence, however, indicates that the diffusive component is mediated by the transient insertion of glucose transporter type 2 (GLUT2) into the apical membrane. This apical GLUT2 pathway of intestinal sugar absorption is present in species from insect to human, providing a major route at high su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
338
2
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(369 citation statements)
references
References 100 publications
11
338
2
6
Order By: Relevance
“…However, we recently demonstrated that sucralose, in two different loads, had no effect on GLP-1, glucose-dependent insulinotrophic polypeptide or insulin secretion, and that it did not elicit any feedback response on gastric emptying in healthy human subjects (5) . While this implies that artificial sweeteners may have no therapeutic benefit in the dietary management of diabetes, other than as a substitute for carbohydrates, it remains possible that sucralose affects small intestinal carbohydrate absorption as a result of its interaction with the sweet taste receptors.Glucose is absorbed from the small intestine through both the Na-dependent GLUT 1 (SGLT1) and the facilitative transporter GLUT2 (6) . Supplementation of the diet with sucralose increases the expression of SGLT1 in the enterocytes of wild-type mice, but not in mice deficient in T1R3 or a-gustducin (4) .…”
mentioning
confidence: 99%
“…However, we recently demonstrated that sucralose, in two different loads, had no effect on GLP-1, glucose-dependent insulinotrophic polypeptide or insulin secretion, and that it did not elicit any feedback response on gastric emptying in healthy human subjects (5) . While this implies that artificial sweeteners may have no therapeutic benefit in the dietary management of diabetes, other than as a substitute for carbohydrates, it remains possible that sucralose affects small intestinal carbohydrate absorption as a result of its interaction with the sweet taste receptors.Glucose is absorbed from the small intestine through both the Na-dependent GLUT 1 (SGLT1) and the facilitative transporter GLUT2 (6) . Supplementation of the diet with sucralose increases the expression of SGLT1 in the enterocytes of wild-type mice, but not in mice deficient in T1R3 or a-gustducin (4) .…”
mentioning
confidence: 99%
“…Transport of fructose across the basolateral membrane of gastrointestinal epithelial cells has been reported to utilize the facilitative hexose transporter GLUT2 (8). GLUT2 is a facilitative transporter for the hexose sugars glucose and fructose that also operates with low affinity and high capacity (38). GLUT2 mRNA expression has been shown to be upregulated by both glucose and fructose (13).…”
Section: Transport Of Fructosementioning
confidence: 99%
“…There are two pathways of glucose absorption, one through SGLT1 and the other the facilitative glucose transporter GLUT2 [4].…”
Section: Ca V 13 Is Present In the Apical Membrane Of Small Intestinementioning
confidence: 99%
“…The second is provided by sweet taste receptors, since the artificial sweetener sucralose doubles glucose absorption by doubling apical GLUT2 without effect on SGLT1 [4].…”
Section: +mentioning
confidence: 99%